PENGARUH ONLINE CUSTOMER REVIEW DAN SHOPPING EXPERIENCE TERHADAP REPURCHASE INTENTION YANG DIMEDIASI OLEH TRUST (STUDI KASUS PADA ONLINE MARKETPLACE) - Annisa Utami Pratiwi; Syafruddin Chan (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
This study aims to determine the Effect of Online Customer Review and Shopping Experiences on Repurchase Intention Mediated by Trust (Case Study on Online Marketplace). The population of this study was the society in Banda Aceh City that had purchased fashion products more than once on the online marketplace. The sampling technique was non-probability sampling with the purposive sampling method. The sample consisted of 230 respondents, but only 191 respondents met the sampling criteria. Data collection equipment was a questionnaire and google form. The analysis technique used was Structural Equation Modeling (SEM) using AMOS software. The results showed that Online Customer Review has a significant effect on Repurchase Intention, but Shopping Experience has no significant effect on Repurchase Intention. Further, Online Customer Review has a significant effect on Trust and Shopping Experience has a significant effect on Trust. This study also found that Trust has no significant effect on Repurchase Intention. Online Customer Review mediated by Trust has no significant effect on Repurchase Intention, and Shopping Experience mediated by Trust has no significant effect on Repurchase Intention.